Electrocution of Eagles in Mongolia - Andrew Dixon; Batbayar Nayambayar; Batbayar Bold; Gankhuyag Purev-Ochir; Amarkhuu Gunga; Munir Virani (Пернатые хищники и их охрана)
Steppe Eagles (Aquila nipalensis) and Golden Eagles (Aquila chrysaetos) are species of conservation and cultural importance in Mongolia. Electrocution at electricity distribution lines is a threat faced by both species across Central Asia. We present the results of power line surveys conducted in the Mongolian steppe region to elucidate temporal patterns of electrocution and specific danger points on power poles for eagles.